المشروع الفلسفي النقدي عند ميشال فوكو - البار,ردينة; مصباحي,فاطمة الزهراء (University of Eloued جامعة الوادي, 2024)
بدأميشال فوكو" مشروعه النقدي" للمجتمع المعاصر باستخدام آليات ومنهج جديد والذي يرتكز على الحفر والتنقيب الأركيولوجيوجنيالوجيا التاريخ،ولعل غرضه من ذلك هو الوصول لاستنطاق أعماق القضايا، والإشكاليات التي باتت تنخر المجتمعات الغربية آنذاك، فقد أعادميشال فوكوالنظر للفلسفة الغربية من خلالالاعتناء بالهامش، والأشياءالمنبوذة،حيث أولى عناية بمجموعة من الإشكاليات التي كان يُنظر لها على أنها هامشية على غرار: الجنون،والجنسانية، السلطة، والرقابةوالعقاب،والتي كانت مفروضة في سياسات الأنظمة القمعية في أوروبا وما سعت إليه هذه الدراسة هو تسليط الضوء على مشروعه النقدي والذي يندرج معرفيا ضمن المساعي الرّامية إلى تغيير الدراسات النقدية القديمة بأدوات منهجية الأركيو-جنيالوجية متجاوزا بذلك المناهج الفلسفية التقليدية ناقدا بذلك البُنى الثقافية الغربية في مجالاتها المختلفة، حيث سعى فوكو إلى العمل على تقويض الميتافيزيقا وتفكيك مقولاتها، إضافة إلى محاولة تحقيق مبدأ العلمية في الدراسات التاريخية والفلسفية. من هنا يكون فوكو قد قدم رؤية مغايرة رفع فيه اللثام عما يجول في عصره، تجعلنا ندرك القضايا والموضوعات المثارة في فكره النقدي فنجدها واضحة ومتكاملة ومنسجمة. . Summary Michel Foucault initiated his "critical project" for contemporary society using new mechanisms and methodologies rooted in archaeological excavation and the historiographical genealogy. His aim was to delve into the depths of issues and problematics plaguing Western societies at the time. Foucault reexamined Western philosophy by focusing on the margins and the marginalized, giving attention to a range of problematics previously considered marginal, such as madness, sexuality, power, surveillance, and punishment, which were imposed in the policies of oppressive systems in Europe. This study sheds light on Foucault's critical project, which falls epistemologically within the efforts to change old critical studies with archaeological-genealogical methodologies, surpassing traditional philosophical approaches, critiquing Western cultural structures in various fields. Foucault sought to undermine metaphysics and dismantle its discourses, as well as attempting to achieve the principle of scientificity in historical and philosophical studies. Thus, Foucault presented an alternative vision that unveiled the issues and topics circulating in his era, enabling us to comprehend the critical aspects of his thought clearly, comprehensively, and cohesively.